Perlindungan Hak Asasi Manusia kepada Masyarakat Adat Papua kaitannya dengan keterlibatan pengelolan SDA - Nouval Dwi Bhara Daksa; Astrid Calista Saraswati Sejahtera; Devi Vanessa Armi Putri; Aida Jihannisa Haidar; Zakia Sofi Salsa Bela Laili (Jurnal Hukum dan Sosial Politik, 2024)
Human Rights are standards to recognise and protect the dignity of all people. Human Rights regulate the coexistence of individuals and each other in society, their relationship with the state, and the obligations of the state towards individuals. In this context, the protection of human rights for indigenous Papuans is very important. The involvement of natural resource management in the protection of human rights is very significant, because natural resource management can have a direct impact on the welfare of indigenous peoples. In this study, we will examine how human rights protection for indigenous Papuans is related to the involvement of natural resource management. The results of this study show that the protection of human rights of indigenous Papuans can be improved through custom-based natural resource management and respect for the rights of indigenous peoples. Therefore, there needs to be greater attention to the protection of human rights and custom-based natural resource management in an effort to improve the welfare of indigenous Papuans.